2016
DOI: 10.1007/s10103-016-1889-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of dental matrix proteins and viability of odontoblast-like cells irradiated with blue LED

Abstract: To evaluate the effect of irradiation with light-emitting diode (LED; 455 nm) on the viability and synthesis of dentin matrix proteins by odontoblast-like cells, MDPC-23 cells were cultivated (10(4) cells/cm(2)) in 24-well culture plates. After 12 h incubation in Dulbecco's modified Eagle's medium (DMEM), the cells were submitted to nutritional restriction by means of reducing the concentration of fetal bovine serum (FBS) for an additional 12 h. Cells were irradiated one single time with one of the following e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In another study, the blue LED was also applied to verify the viability and synthesis of dentin matrix proteins by odontoblast-like cells. The protocol used consisted in a single application using equipment with an intensity of 20 mW/cm and a dose of light equivalent to 0.5, 2, 4, 10, or 15 J/cm 2 and it was observed that blue LED did not present bio stimulatory capacity on odontoblast-like cells 45 .…”
Section: Blue Led -400-470 Nmmentioning
confidence: 99%
“…In another study, the blue LED was also applied to verify the viability and synthesis of dentin matrix proteins by odontoblast-like cells. The protocol used consisted in a single application using equipment with an intensity of 20 mW/cm and a dose of light equivalent to 0.5, 2, 4, 10, or 15 J/cm 2 and it was observed that blue LED did not present bio stimulatory capacity on odontoblast-like cells 45 .…”
Section: Blue Led -400-470 Nmmentioning
confidence: 99%
“…Cell viability was determined using the methyl tetrazolium assay (tetrazoline 3-(4,5-dimethylthiazol-2-yl) -2,5-diphenyl bromide), which determines the activity of succinic dehydrogenase (i.e., a measure of cellular (mitochondrial) respiration) and represents the rate of viability. This well-standardized protocol has been previously described in detail [2,18,20,30].…”
Section: Cell Viability (Mtt Assay)mentioning
confidence: 99%
“…Different modalities of photobiomodulation have been employed as adjuvant treatments for bone loss, myalgia, skin burns, spinal cord injury, and pulp repair [6][7][8][9][10]. Clinical and laboratory studi es have evaluat ed the eff ect of photobiomodulation on the healing of different tissues, such as the muscle and cartilage [11,12], neuronal cells [13,14], bone [15,16], and the dentin-pulp complex [2,17,18]. Photobiomodulation using light emitting diodes (LED) has been widely assessed in dentistry and is considered a potential adjuvant treatment for stimulating pulpal healing [2,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation